Psycho-social Correlates of Driving Behavior: A Masculinity Perspective - Noreen, Mehwish; Noor, Sara (Pakistan Journal of Humanities and Social Sciences, 2023)
The goal of the current study was to examine the relationship between identity traits, manliness, and aggressive driving in young male drivers. Manliness was hypothesized to mediate the relationship between identity traits and aggressive driving. It is generally agreed that there will likely be a relationship between identity features, manliness, and forceful driving in young male drivers, and that manliness will probably operate as an intermediary in that relationship. It is a cross-sectional co-relational research study. A total of 150 young male drivers made up the sample. Purposive sampling was used to gather the sample from various Lahore institutions. The Doing Masculinity Composite Scale (DMCS), the Ten-Item Personality Inventory (TIPI), and the Aggressive Driving Behavior Questionnaire (ADBQ) are among the measures. Structural Equation Modelling (SEM) was used to examine the mediating effect of masculinity between aggressive driving behavior and personality factors. Pearson product moment correlation was utilized to evaluate the relationship between the study variables. The goal of this study is to identify any potential psycho-social causes of aggressive driving in order to develop a strategy to curb this behavior while improving men's social perception.